The law relating to banking - Reeday, T. G.; Great Britain; Great Britain (London : Butterworths, 1972)
The book deal with the contract, agency, partnership, companies, bankruptcy and other issues relating to law and banking, and the book is recommended as part of the syllabus used in the Institute of Bankers.
"Bills of exchange act 1882": p. 305-392, 412-421.
"Cheques act 1957": p. 393-411.
gp. 24/01/2019
Loan
Keywords: Banking law